Visual trends and hot research on the relationship between intestinal microbiota and major lipids: a bibliometric analysis - Sun, Weiming; Wan, Keqi; Gui, Jiawei; Jin, Guoqiang; Shuai, Lang (Frontiers in Microbiology, 2024)
The association between intestinal microbiota and lipids has garnered significant scholarly interest. This study analyzes pertinent literature on intestinal microbiota and lipids to offer scientific guidance for future advancements and research directions.Methods: Articles focusing on intestinal microbiota and lipids were obtained from the Web of Science Core Collection (WoSCC). Following a rigorous screening process, 12,693 articles were included in the study. The collected data was processed comprehensively and visually analyzed using various academic tools such as CiteSpace, VOSviewer, R software, and Scimago Graphica.The field of intestinal microbiota and its relationship with major lipids has witnessed a significant surge in scholarly attention, as indicated by the upward trend observed in related articles.Among countries, China had emerged as the leading contributor in publication output, with Chinese Acad Sci being the most prolific institution in this field. Notably, Nutrients and Nature were the prominent journals that published many articles and garnered the highest number of co-citations.Scholars have widely recognized Patrice D Cani's notable contributions in this field. Current research endeavors have focused on obesity, insulin resistance, metabolism, growth performance, the gutbrain axis, and others.Conclusions: Our analysis identified four primary research trends: 'biochemical pathways', 'exploration of diseases', 'intervention and effect, and 'health and diet'. Future scholars must devote more attention to intestinal microbiota and major lipids to advance our understanding of human health.